Characteristics of the Special Physical Fitness of Paddlers at a Distance of 200 m - Diachenko, Andrii; Rusanova, Olga; Guo, Pengcheng; Kong, Xianglin; Huang, Zijian; Guo, Jia (Physical Education Theory and Methodology, 2021)
The aim of the study. The overall goal of this manuscript was to gain a better understanding of differences in the level of functional support for special endurance for paddlers of uniform groups (in terms of sports qualification): men kayakers, men canoeists, and women kayakers who specialize in a distance of 200 m. Material and methods. 20 qualified paddlers’ level of functionality is being assessed, among them are a group of elite athletes, the members of the Chinese national team and winners of the 2018 Asian Games. Results. The important feature of the analysis is the evaluation of the structure of the ergonomic power of a 30-second maximum load. Estimating the average value of the ergometric power of work for 25-30 seconds of operation in accordance with the average power of the entire 30-second load made it possible to determine the ratio of the anaerobic alactic and lactic abilities of the athletes, taking into account the requirements of a 200-meter race for canoe and kayak paddlers. A significant range of individual differences in the indices of reactive properties of the cardiorespiratory system, which are determined by the ratio of the partial pressure of СО2 and the maximum level of pulmonary ventilation (VE/PaCO2) during the10 and 30 second test task, attracts attention. The range of VE/PaCO2 indicators was: the relation of partial pressure СО2 to pulmonary ventilation in the 10 s test – 2.3 ± 0.8 for men kayakers; 2.3 ± 0.7 for men canoeists; 2.2 ± 0.5 for women kayakers; the relation of partial pressure СО2 to pulmonary ventilation in the 30 s test – 3.9 ± 1.0 for men kayakers; 3.8 ± 1.1 for men canoeists; 3.6 ± 0.7 for women kayakers. Conclusion. The results of the study indicate differences in the level of functional support for special endurance for paddlers of uniform groups (in terms of sports qualification): kayakers and canoeists who specialize in a distance of 200 m.